Durability of interior renderings in schools: optimization of envelope insulation for mitigation of mould growth risk - Nuno Ramos (2013)
A high standard education is, nowadays, a clear objective for any modern society. In Portugal, the retrofit of educational buildings has an enormous relevance as demonstrated by the Program for Retrofit and Upgrade of High Schools. Educational buildings specific characteristics such as high occupancy rates and high amount of time children spend in classrooms make them a special case compared to other buildings. Mould growth on envelope surfaces is frequently observed in these buildings, reducing the expected durability of renderings and coatings. The present work consisted of two main lines of research: one of simulation and other of optimization. The simulation part included modelling of Interior Surfaces Temperature, Indoor Air Temperature and Relative Humidity variation, before and after a hypothetical retrofit process. Optimization techniques were applied in the definition of insulation thickness to be numerically tested in the after retrofit scenario. The objective was to minimise insulation thickness in each building element of the envelope. The constraints were derived from the control of surface temperature values that would result in mould growth risk.